Analysis of Student Readiness in E-Learning-Based Ecological Learning - Irma Suryani; Hasanuddin Hasanuddin; Ismul Huda; Samingan Samingan; Abdullah Abdullah (Postgraduate, University of Mataram, 2022)
In the 21st century, learning does not have to be in the real class. In this condition, teachers and students must be able to communicate and adapt to the development of information technology (IT). It is expected that teachers and students must be able to master the use of IT or the internet in e-learning. The purpose of this study was to determine the readiness of students in e-learning-based ecological learning.Â This approach is a quantitative approach with the type of research being descriptive. The method and design of survey research. The sample of this research is the total population of 340 students. The research instrument is a closing questionnaire, which is the result of adaptation from Tuntirojanawong research. In this study, the data collection was a questionnaire through the website:Â Aceh Online Learning System: (SpadaAceh). The statistics used for the analysis of the questionnaire data are mean and standard deviation. The results of the study on the student readiness variable include 5 (five) indicators namely technology access (mean 3.52), technology skills (mean 3.51), learning ability (mean 3.65), time management skills (mean 3.51),Â and learning motivation (mean 3.51). The five indicators fall into the category